GEOECOLOGICAL RESEARCH OF THE BLACK SEA ESTUARIES AS A COMPONENT OF THE AZOV-BLACK SEA BASIN GEOECOSYSTEM - Iemelianov, V.; Ivanik, O.; Kulaha, T.; Kostiuchyk, Ye.; Drozdova, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Black Sea estuaries are unique natural formations that havegreat geoecological and recreational importance. But their ecological state is almost critical and requires developing effective measures to preserve them and restore the geoecological balance. On the basis of literary and field materials, the article analyzes the information about the history of research of estuaries within the northwest coast of the Black Sea. The current state and problematic situations in the study of their morphology, dynamics and regime are determined, the current problems for each estuary are emphasized. On the basis of field geological and geomorphological investigations and remote sensing data, the features of gravitational geological processes within the coastal zones are characterized. Changes in the morphology of the coastline and estuary areas during 2015–2020 are analyzed. Modern hydrological characteristics and features of ecological condition of these estuaries are given. Perspectives of further research of these objects are determined. To preserve the natural value of the estuaries as a unique transition zone between sea and land (geoecoton), the geoecological research approachis proposed to use.